Journal Watch - Jennifer A. Herzog (American Society for Microbiology, 2015)
In this section, I provide articles on recent developments and new technology used in microbiology and related fields. I also post articles that may help you bring new information or techniques into your laboratory or classroom via case studies or lab exercises. I hope you find this information useful, and I encourage you to send suggestions, questions, or comments to me at herzogja@herkimer.edu. I look forward to hearing from you!